Diagnostic Value of Gynecologic Ultrasonography as A Malignancy Predictor in Children's Ovarian Tumor - Ni Made Putri Suastari; Pande Putu Yuli Anandasari; Putu Patriawan; Ni Nyoman Margiani; Firman Parulian Sitanggang; I Gde Raka Widiana (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
The incidence of ovarian malignancy is rare in children, with proportions between 16-55%. A gynecologic ultrasonography score is expected to increase accuracy and be able to diagnose malignancy earlier. By using a retrospective cross-sectional study design, this study is a diagnostic test to assess ultrasonography examination as a predictor of malignancy with histopathological examination as the gold standard. The study subjects were 45 children admitted from July 2017 to December 2020. Characteristics of the subjects were obtained from medical records, gynecologic ultrasonography images were accessed from PACS, and histopathological results were obtained from SIMARS. The gynecologic ultrasonography images were scored by two observers using a scoring table. Variables assessed consisted of inner wall structure, wall thickness, septa, morphology, tumor vascularization and ascites. The data will then be analyzed, determining the optimal cut-off score, sensitivity, specificity, accuracy, and positive and negative predictive value. AUC value of 0.92 using a cut-off ≥14 obtained 15 malignant subjects and 1 benign subject and resulted in a sensitivity of 78.9%, specificity of 96.2%, a positive predictive value of 93.8%, a negative predictive value of 86.2%, and accuracy of 88.89%. It can be concluded that the diagnostic value of gynecologic ultrasonography examination as a predictor of malignant ovarian tumors in children was remarkable.